Bio-inspired crosslinking and matrix-drug interactions for advanced wound dressings with long-term antimicrobial activity - Dhand, Chetna (2017)
There is a growing demand for durable advanced wound dressings for the management of persistent infections after deep burn injuries. Herein, we demonstrated the preparation of durable antimicrobial nanofiber mats, by taking advantage of strong interfacial interactions between polyhydroxy antibiotics (with varying number of single bondOH groups) and gelatin and their in-situ crosslinking with polydopamine (pDA) using ammonium carbonate diffusion method. Polydopamine crosslinking did not interfere with the antimicrobial efficacy of the loaded antibiotics. Interestingly, incorporation of antibiotics containing more number of alcoholic single bondOH groups (NOH ≥ 5) delayed the release kinetics with complete retention of antimicrobial activity for an extended period of time (20 days). The antimicrobials-loaded mats displayed superior mechanical and thermal properties than gelatin or pDA-crosslinked gelatin mats. Mats containing polyhydroxy antifungals showed enhanced aqueous stability and retained nanofibrous morphology under aqueous environment for more than 4 weeks. This approach can be expanded to produce mats with broad spectrum antimicrobial properties by incorporating the combination of antibacterial and antifungal drugs. Direct electrospinning of vancomycin-loaded electrospun nanofibers onto a bandage gauze and subsequent crosslinking produced non-adherent durable advanced wound dressings that could be easily applied to the injured sites and readily detached after treatment. In a partial thickness burn injury model in piglets, the drug-loaded mats displayed comparable wound closure to commercially available silver-based dressings. This prototype wound dressing designed for easy handling and with long-lasting antimicrobial properties represents an effective option for treating life-threatening microbial infections due to thermal injuries.